2004
DOI: 10.1152/ajprenal.00158.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protection of transplant-induced renal ischemia-reperfusion injury with carbon monoxide

Abstract: Carbon monoxide (CO), a product of heme metabolism by heme oxygenases, is known to impart protection against oxidative stress. We hypothesized that CO would protect ischemia-reperfusion (I/R) injury of transplanted organs, and the efficacy of CO was studied in the rat kidney transplantation model. A Lewis rat kidney graft, preserved in University of Wisconsin solution at 4 degrees C for 24 h, was orthotopically transplanted into syngeneic rats. Recipients were maintained in room air or exposed to CO (250 ppm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
139
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 47 publications
10
139
2
4
Order By: Relevance
“…This observation suggests that these compounds are sufficiently concentrated in the kidney to increases local levels of CO in the absence of any decreases in COHb levels. This aspect of these compounds makes them attractive alternatives to CO inhalation therapy, which requires high levels of COHb in the blood to be achieved to be effective (12). We also found that these compounds seem to lose their beneficial qualities when administered after the ischemic episode.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This observation suggests that these compounds are sufficiently concentrated in the kidney to increases local levels of CO in the absence of any decreases in COHb levels. This aspect of these compounds makes them attractive alternatives to CO inhalation therapy, which requires high levels of COHb in the blood to be achieved to be effective (12). We also found that these compounds seem to lose their beneficial qualities when administered after the ischemic episode.…”
Section: Discussionmentioning
confidence: 75%
“…There have been several reports that inhalation of CO can be protective against acute rejection of intestine, lung, and kidney transplants (11,12,23,24). The protective actions of CO inhalation in transplantation are associated with a decrease in inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies examined the role of HO-1 and CO in kidney injury, and the functional role of CO in the context of renal fibrosis has not been previously examined. HO-1 overexpression or CO administration has been shown to protect experimental kidney transplants from ischemia-reperfusion injury (4,30). Moreover, the administration of CO donor compounds, namely carbon monoxide-releasing molecules (CORM-3), protected against cisplatin nephrotoxicity and ischemia-reperfusion-induced renal injury (44,47).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been shown that administration of CO can protect endothelial cells, smooth muscle cells, and neurons against apoptosis in models of ischemic injury (Dore et al, 2000;Neto et al, 2004). Conversely, blockade of HO activity can exacerbate injury in such animal models.…”
Section: Endogenous Neurotoxins and The Pathological Second Phase Of mentioning
confidence: 99%